دراسة تأثير بعض هرمونات النمو النباتية في تحريض تشكل الكالوس عند نبات النعناع البري Mentha pulegium - العوض دانيال; يازجي ميساء; إبراهيم ريم (Latakia University Journal -Biological Sciences Series, 2018)
The objective of this research is to induce callus formation of Mentha pulegium in vitro. Seedlings have grown in MS medium, then nodal, leaf and stem explant of seedlings were planted with 0.5- 1cm 0n MS medium with various concentrations of auxin (2,4-D - NAA) in combination with various concentrations of cytokinin BAP. The cultures were maintained in plant growth incubator at temperature 25±2 °C with a photoperiod of 16 hours light (2000-2500 lux) and 8 hours dark. Experiments have proved that the MS medium with 1 mg/l 2,4-D in combination with 0.5 mg/l BAP was the best for forming calluses on 98.33% from nodal explant and97% from stem cutting, whereas using 1 mg/l of 2,4-D with 0.8 mg/l 0f BAP was the best for callus induction from leaf cutting. The MS medium supplemented with 1mg/l of NAA and 0.5 mg/l of BAP was good for callus induction at high percentage 98% for nodal explants. The results also have proved that the nodal explants were the best plant parts used to form the callus on the MS medium in most hormone concentrations, all BAP concentrations used in combination with 1 mg / l of 2,4-D were suitable for inducted callus formation from nodal explant in percentage ranged between 98 - 98.33%. The calluses can be used to obtain extract crud plant in good amount. تم في هذا البحث تنمية بادرات النعناع البري مخبرياً على الوسط المغذي MS ومن ثم زراعة العقد الساقية والقطع الورقية والساقية لتلك البادرات على الوسط MS المضاف إليه تراكيز مختلفة من الأوكسينات(NAA- 2,4-D) بالاشتراك مع تراكيز مختلفة من السيتوكينين BAP، حضنت الزراعات جميعها في حاضنة نمو نباتية في الدرجة 25±2مº وبإضاءة 16 ساعة بالتنناوب مع 8 ساعات ظلام وبشدة ضوئية تراوحت بين 2500-3000 لوكس. أثبتت التجارب أن الوسط المغذي MS المضاف إليه 1 مغ/ل من الأوكسين 2,4-D بالاشتراك مع 0.5 مغ/ل منBAP كان الأفضل لتشكل الكالوس حيث بلغت النسبة المئوية على العقد الساقية98.33 %، وعلى القطع الساقية 97%، وعند استخدام 1 مغ/ل من 2,4-D مع 0.8 مغ/ل منBAP بلغت النسبة 97.66% بالنسبة للقطع الورقية، وكذلك كان الوسط MS المضاف إليه NAA بتركيز 1مغ/ل بالاشتراك مع 0.5 مغ/ل من BAP جيداً لتشكل الكالوس وبنسب مرتفعة وكان أفضلها 98% للعقد الساقية. تبين النتائج أيضاً أن العقد الساقية أفضل الأجزاء النباتية المستخدمة لتشكل الكالوس على الوسط MS في معظم التراكيز الهرمونية، حيث كانت جميع تراكيز BAP المستخدمة بالاشتراك مع 1مغ/ل من 2,4-D مناسبة لتشكل الكالوس بدءاً من العقد الساقية وبنسبة تراوحت بين 98.33-98%. يمكن استخدام الكالوس المتشكلة من العقد الساقية في الحصول على الخلاصة الخام وبمردود جيد.